2019
DOI: 10.1155/2019/4925682
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Pharmacological Activities and Potential Medicinal Benefits of Geniposide

Abstract: Geniposide is a well-known iridoid glycoside compound and is an essential component of a wide variety of traditional phytomedicines, for example, Gardenia jasminoides Elli (Zhizi in Chinese), Eucommia ulmoides Oliv. (Duzhong in Chinese), Rehmannia glutinosa Libosch. (Dihuang in Chinese), and Achyranthes bidentata Bl. (Niuxi in Chinese). It is also the main bioactive component of Gardeniae Fructus, the dried ripe fruit of Gardenia jasminoides Ellis. Increasing pharmacological evidence supports multiple medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 88 publications
(93 reference statements)
0
37
0
Order By: Relevance
“…Previous studies reported that geniposide exhibited antiapoptotic activity on a number of normal cells under different stimulation, while exerted proapoptosis activities in tumor cells. [ 14 ] It has been proved to play outstanding antitumor activities on human oral squamous carcinoma, osteosarcoma, and glioma through inhibiting cell proliferation and promoting cell apoptosis. [ 20‐22 ] Besides that, Galvez et al [ 49 ] indicated that geniposide was able to exert anticancer activity on other tumors such as renal adenocarcinoma, breast adenocarcinoma, and melanoma by stabilizing covalent attachment of the topoisomerase I subunits to DNA at sites of DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that geniposide exhibited antiapoptotic activity on a number of normal cells under different stimulation, while exerted proapoptosis activities in tumor cells. [ 14 ] It has been proved to play outstanding antitumor activities on human oral squamous carcinoma, osteosarcoma, and glioma through inhibiting cell proliferation and promoting cell apoptosis. [ 20‐22 ] Besides that, Galvez et al [ 49 ] indicated that geniposide was able to exert anticancer activity on other tumors such as renal adenocarcinoma, breast adenocarcinoma, and melanoma by stabilizing covalent attachment of the topoisomerase I subunits to DNA at sites of DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11,12 ] Geniposide (CAS number: 24512‐63‐8; Figure 1) is the main active ingredient separated and purified from the fruit of Gardenia jasminoides Ellis. [ 13 ] Earlier research reported that geniposide possessed beneficial activities, [ 14 ] such as anti‐inflammation, [ 15 ] antidiabetes, [ 16 ] antiangiogenesis, [ 17 ] antitumor, [ 18 ] and neuroprotection. [ 19 ] For antitumor activity, Qian et al [ 20 ] indicated that geniposide could inhibit cell proliferation and induce cell apoptosis of human oral squamous carcinoma HSC‐3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Geniposide is the major bioactive component of herb Gardeniae Fructus which exhibits a wide range of pharmacological functions including neuroprotective, hypoglycemic, hepatoprotective, anti-inflammatory, analgesic, cardio-protective, antioxidant, immune-regulatory, antithrombotic, and antitumoral effects (Zhou et al, 2019b). The herb has long been used as choleretic to treat jaundice in Chinese history and modern research also reveals that geniposide attenuates APAP-induced liver injury in mice (Yang et al, 2019).…”
Section: Geniposidementioning
confidence: 99%
“…Geniposide, a typical iridoid compound, has a high content of G. jasminoides and is one of the effective ingredients. Geniposide can exert many pharmacological effects, such as antidiabetic, antioxidant, neuroprotection, and liver protection properties [ 16 ]. In the primary hippocampal neurons of middle-aged Alzheimer’s disease mouse models, geniposide can inhibit the toxic effects of cholinergic defects by increasing choline acetyltransferase activity and reducing acetylcholinesterase activity to play a neuroprotective effect [ 17 ].…”
Section: Introductionmentioning
confidence: 99%